The forms of canonical dependence of an individual hermit from the church hierarchy in the post-Tridentine sources of the law of the Latin Church - BIDER, MARCIN (Prawo Kanoniczne, 2019)
The object of the article was to present forms of the canonical dependence of an individual and independent hermit from the Church hierarchy in the post-Tridentine sources of the Latin Church. The historical and legal method is used in this scientific article. Theological and social-political transformations during the post-Tridentine period in Europe contributed to the fact, that independent and individual eremitic life, flourishing in Catholic countries still in the 17th century, lost so much in its intensity in the 18th century that the French Revolution contributed to its extinction. Resident bishops, erecting or approving the non-order hermits’ congregations, attempted to reform the independent and individual eremitic life. The canonists taking into account, among others things, the non-order nature of individual and independent eremitism, were not very interested in it. The author came to the conclusion that the legislation of the resident bishops attempted to make individual and independent eremitic or anchoritic life canonically similar to religious life.